Investigating Mediating Effect of Training on the Relationship of Ai Application Factors and Crisis Management for Abu Dhabi Police Department - Alshamsi, Abdulla Mohammed Saif Ali; Omar, Abdul Jalil (Tropical Scientific Journal, 2025)
Objective: This study investigates the mediating effect of AI Training on the relationship between AI application factors and Crisis Management within the Abu Dhabi Police Department. It aims to enhance understanding of how AI integration, particularly through training, can improve crisis response effectiveness. Research Method: A quantitative approach was employed using Structural Equation Modeling; Partial Least Squares (SEM-PLS) via SmartPLS software. Data were collected from 346 employees working in AI-utilized departments within the Abu Dhabi Police. Findings: The results demonstrate a robust model with moderate explanatory power and good model fit. AI Training significantly mediates the relationship between Predictive Policing, Data Analysis, Emergency Response, and Surveillance with Crisis Management. However, AI Training does not mediate the relationship between Security and Crisis Management. These findings suggest that AI Training plays a crucial role in optimizing crisis management outcomes. Originality: This study provides empirical insights into the specific role of AI Training as a mediating factor in AI-based crisis management frameworks, particularly within law enforcement settings. It contributes to a deeper understanding of how training can bridge AI application and practical crisis response